Fungal nasopharyngitis masquerading as nasopharyngeal mass in an immunocompetent patient: a case report - Karthikeyan, P.; Sivanand, Nikhil; Vijayan, Neelima; Kumar, Vishnu; Srinivasa, Nanditha; Raghavan, Vignesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Isolated nasopharyngeal candidiasis in an immunocompetent host, has not been reported in literature. This is a case of a 48 year old lady with no comorbidities who presented with a mass in the nasopharynx mimicking nasopharyngeal malignancy. Endoscopic debridement and biopsy revealed necrotic tissue with fungal ball composed of filamentous hyphae suggestive of aspergillus and budding yeast form of Candida. A diagnosis of fungal nasopharyngitis was made and started on antifungal therapy for 6 weeks following which patient is relieved of symptoms.